Improving access to health care amongst vulnerable populations: a qualitative study of village malaria workers in Kampot, Cambodia - Marco Liverani; Chea Nguon; Ra Sok; Daro Kim; Panharith Nou; Sokhan Nguon; Shunmay Yeung (BMC, 2017)
Abstract Background There is growing interest in the expansion of community health workers programmes in low- and middle-income countries as a cost-effective approach to address shortages of health professionals. However, our understanding of the reception of large-scale programmes and how to improve them remains limited, with knowledge gaps about factors that may promote or discourage equitable access to services. This paper examines the case of the Village Malaria Workers (VMW) programme in Cambodia, an extensive community-based intervention for the management of malaria cases in remote rural areas. Method Fieldwork was conducted in Kampot province, in six case villages characterised by different programme configuration, population size, and distance to the nearest public health facility. In these locations, in-depth interviews (n = 71) with VMWs, village authorities, and residents were conducted to identify facilitators and challenges to service utilisation. Data analysis was informed by a conceptual framework based on five domains of access to services: awareness, accessibility, accommodation, availability, and acceptability. Results Factors that influenced the utilisation of VMW services in our research sites include: the nature of dissemination activities and their ability to reach different population groups; the village topography and the changing road infrastructure; the involvement of VMWs in other community roles and activities; perceptions about the type of disease after the onset of symptoms; the need for comprehensive diagnosis and care; perceptions about the status of VMWs as medical providers; length of VMW appointment. Conclusions This study highlights the complexity and diversity of contextual factors that may influence the uptake of a community health programme. As in other countries, continued use of lay health workers in Cambodia to deliver diagnostic and curative services has the potential for great health and economic impact. However, further consideration should be given to the problem of access in different categories of residents and different contexts of implementation. In addition, a comprehensive mapping of changes in disease epidemiology, road infrastructure and the geography of access to services is crucial to inform policy development in this area.